Випуск 9(25). Review of transport economics and management - (:unkn) unknown (Український державний університет науки і технологій, Дніпро, 2023)
UKR: Збірник висвітлює результати наукових досліджень з актуальних проблем розвитку й трансформації соціально-економічних систем, підвищення їх конкурентоспроможності; представлено теоретико-методологічні засади оптимізації управлінських процесів і виробничо-господарської діяльності підприємств; розкрито сучасні підходи до вдосконалення методів і моделей управління в різних сферах економіки за напрямами: економіка та управління національним господарством; економіка і менеджмент підприємств транспорту; фінанси й облік; поведінкова економіка; цифрова економіка; математичні й інструментальні методи в економіці.

ENG: The collection covers the results of scientific research on economic issues of development and reformation of socio-economic systems, enhancing their competitiveness; theoretical and methodological approaches to optimization of processes of management and production and economic activity of enterprises; scientific approaches to the development and improvement of management methods and models in various fields of activity under the headings: Economics and Management of National Economy, Economics and Management of Transport Enterprises, Finance and Accounting, Behavioral Economics, Digital Economics, Mathematical and Instrumental Methods in Economics.
Issue 9(25). Review of transport economics and management
Keywords: економіка та управління національним господарством; економіка і менеджмент підприємств транспорту; фінанси й облік; поведінкова економіка; цифрова економіка; математичні методи в економіці; інструментальні методи в економіці; economics and management of national economy; economics and management of transport enterprises; finance and accounting; behavioral economics; digital economics; mathematical methods in economics; instrumental methods economics; КФОП; SOCIAL SCIENCES; SOCIAL SCIENCES::Business and economics